Pengembangan Bahan Ajar Kimia Materi Larutan Asam dan Basa Berbasis Chemo Edutainment Untuk Siswa SMK TI Kelas XI - Chairiah Chairiah; Albinus Silalahi; Wesly Hutabarat (Pascasarjana Universitas Negeri Medan, 2016)
Abstract. This research aims to know the feasibility of Chemistry Materials for grade eleventh SMK in the second semester for acids and bases solution topic that exist today in accordance with BSNP (National Education Standards Beureu); to know the feasibility of Chemistry Materials based chemo edutainment for students grade eleventh SMK in the second semester for acids and bases solution topic in accordance with BSNP (National Education Standards); to know the differences of increase learning outcomes that learned with Chemistry Materials based chemo edutainment for acids and bases solution topic compared than learning outcomes that learned with Chemistry Materials without the development; and to know the differences of increase students motivation learning outcomes that learned with Chemistry Materials based chemo edutainment for acids and bases solution topic compared than students motivation learning outcomes that learned with Chemistry Materials without the development. This type of research was development using a model ADDIE (Analysis, Design, Development, Implementation and Evaluations). The population in this research was all of students grade eleventh SMK. The sample in this research was SMK Negeri 1 Stabat much as two classes and have totaling students is 64 . The results showed that: (1) the chemistry materials publisher X and Y for acids and bases solution topic in accordance with BSNP (National Education Standards) is quite feasible, but there are some that need to be developed; (2) Chemistry materials that developed for acids and bases solution topic has a decent based on the feasibility of standardizing the contents is 4.11, Language feasibility is 4.24, Presentation feasibility is 4,16 Graphically feasibility is 4,42; (3) there are significant differences in student learning outcomes with the implementation of the chemistry materials based chemo edutainment was better than the learning outcomes of students with Chemistry materials without the development (Sig <α and tcount> t table) is 0.00 <0.05 and 4.013> 1.694; (4) the increase of students motivation learning outcomes with the implementation of the chemistry materials based chemo edutainment was higher (77,92) than the students motivation learning outcomes with Chemistry materials without the development (63,78).Keyword: chemistry teaching materials, solution of acids and bases, chemo edutainment, learning outcomes, motivation to learn